Histomorphological effects of sodium arsenite on uterus of rats - Mir, Amaidah; Butt, Hammad Ahmed; Yasmeen, Maria; Saleem, Anber; Minhas, Ruqqia Shafi; Abbasi, Sumaira (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Arsenic is highly toxic agent and a risk factor for disease and disability. Arsenic is present in drinking water of many developing and developed countries including Pakistan and due to rapid industrialization its quantity in soil and water is increasing day by day. Methods: In an 18 month study in which we took two principal groups, labelled as control group A and experimental group B. The animals of experimental group B were administered 4 µg of sodium arsenite dissolved in 10 ml of distilled water by oral gavage daily for 14 days. The uterus was removed and processed for paraffin embedding and stained with hematoxylin and eosin (H and E). The histological parameters; uterine luminal diameter, height of uterine luminal epithelium, area occupied by epithelial component of uterine glands and the thickness of myometrium were measured and evaluated by civil AutoCAD 2013 software. The data was analyzed statistically with the statistical package for social sciences (SPSS). Results: Histological results showed the degenerative effects. The luminal diameter of uterine horns was reduced in experimental animals. The height of uterine epithelium was reduced. Area occupied by epithelial component of uterine glands was reduced along the reduction in the thickness of myometrium. Conclusions: The histological abnormalities observed in uterus showed that the degenerative effects may be due to oxidative stress produced by the exposure to sodium arsenite. As sodium arsenite produces the oxidative stress by the formation of free radicals and by the denaturation of proteins.